Electric Car Battery Waste in Indonesia: Projections and Management Policies - Hadinata*, Jaka; Sodri, Ahyahudin; Koestoer, Raldi Hendrotoro Seputro (Graduate School of Universitas Syiah Kuala, 2025)
Global trends in electric vehicle adoption have been increasing significantly in recent years. In Indonesia, the government has issued various policies to encourage the use of electric cars. However, anticipation of the environmental impact of this program has not yet received serious attention. Current regulations regarding battery waste management still refer to existing regulations governing hazardous and toxic waste. This study aims to forecast the potential of battery waste from electric cars in the future and provide policy recommendations to establish a sustainable electric car program. The methods of analysis employed include material flow analysis and policy content analysis. Based on three scenarios (low, medium, and high adoption scenarios), the analysis results show a significant increase in battery waste in all scenarios from 2025 to 2040. The increase in active materials, aluminum, and copper waste could exceed 50 times during this period. Electrolyte, plastic, and steel waste also increase substantially, with growth reaching 3050 times. Although relatively small in volume, rare earth metals are projected to rise 19 times. By 2040, the potential of battery waste is estimated to reach 1,998,911 tons in a low adoption scenario, 2,600,540 tons in a medium adoption scenario, and 3,170,517 tons in a high adoption scenario. The result of policy content analysis of the electric vehicle regulations issued by the Indonesian government since 2019 demonstrates that efforts to enhance electric vehicle adoption will become the main focus for the government in the coming years. A thematic mapping of policies related to 20 electric vehicle regulations published during this period reveals that only three regulations address environmental issues. This study indicates the need for policy improvements by formulating specific derivative regulations that govern electric car battery waste management.